Antibacterial Activity and Chemical Composition of Essential Oil of Athamanta sicula L. (Apiaceae) from Algeria - I. Labed; S. Chibani; Z. Semra; A. Kabouche; T. Aburjai; R. Touzani; Z. Kabouche (E-Journal of Chemistry)
Essential oil extracted from fresh aerial parts of Athamanta sicula L. (syn. Tingara sicula) was analysed by gas phase chomatography coupled to mass spectrometry (GC-MS). The main constituents were: germacrene B (88.5%) and apiol (4.9%). Comparing with the tested bacteria, the growth of Escherichia coli and Klebsiella pneumoniae strains was more inhibited by the essential oil of A. sicula.